THE STATE ANALYSIS OF THE ANTI-EROSION INSTALLATIONS CARRIED OUT FOR THE PROTECTION OF THE CITY OF HASSI EL GHALA (WILAYA OF AIN TEMOUCHENT, ALGERIA) AGAINST FLOODS - ZEKRI, Nadia; SID, Ahmed Soufiane (International Journal of Innovative Technologies in Social Science, 2023)
Water erosion is an inevitable natural phenomenon that sometimes causes very serious damage to infrastructure (towns, roads, hydraulic dams, etc.). Things’ which require anti erosion restorations, in the watersheds of these infrastructures, to protect them. The objective of this research is to perform an is analysis of the state and effectiveness of some anti-erosion restorations, in particular of the thresholds of torrential correction, carried out since 1986 to protect the city of Hassi El Ghalla (region of Ain Temouchent) against floods. The methodology adopted was based on direct observations in the field, taking photos and collecting data at the level of forest conservation in the wilaya of Ain Témouchent. The results obtained revealed a positive assessment of the state of the anti-erosion facilities. The torrential correction weirs and the stepped terraces are mostly in good condition. The vegetation cover is quite dense and the soils are more vulnerable to sheet erosion, qualified as less dangerous compared to linear erosion and mass erosion. The implementation of anti-erosion actions has highly protected the town of Hassi El Ghala against flood. But the forest administration must bring some rehabilitations to these actions and maintain their in sustainability for more efficiency.